Viral manipulation of the HLA class I antigen processing and presentation pathway - Nolan, Dominic S; Altenburg, Arwen F (Frontiers in Immunology, 2025)
Major histocompatibility complex (MHC, human leukocyte antigen [HLA] in humans) class I molecules present peptides at the cell surface to cytotoxic immune cells. Peptides are generated and selected for MHC class I presentation in the antigen processing and presentation (APP) pathway. Recognition of a foreign peptide in the context of MHC class I by CD8+ T cells results in target cell lysis. While CD8+ T cells don’t provide sterile immunity, they are pivotal in viral infections by clearing infected cells and may impact disease duration and severity, and virus spread. Additionally, MHC class I molecules act as ligands for NK cell receptors, which similarly play an important role in the control of virus infections through cytotoxic activity and cytokine production. To evade immune recognition, viruses have developed strategies to modulate MHC class I levels by targeting MHC molecules directly or by disrupting components of the APP pathway. Herpesviruses, large DNA viruses that encode numerous immunoevasins, are notorious for disrupting virtually every stage of the MHC class I APP pathway. Over the years, it has become clear that a wide range of other viruses also have evolved targeted mechanisms to modulate MHC class I or components of the APP pathway to evade cytotoxic immune responses. Here, we review the literature on targeted viral manipulation of HLA class I, including non-classical HLA molecules, and modulation of components of the APP pathway by viruses infecting humans.